ANALISIS FAKTOR PENYEBAB KEMACETAN PADA RUAS JALAN SIMPANG TUNGGUL HITAM SAMPAI DENGAN DEPAN BASKO GRAND MALL, AIR TAWAR, KOTA PADANG, SUMATERA BARAT - Eko Prayitno; Veronika Veronika (JURNAL PLANOLOGI DAN SIPIL (JPS), 2019)
Congestion occurs due to increased vehicle and very rapid population growth in the city of Padang. The problem of congestion is generally caused by the physical limitations of urban land, economic and social aspects and culture of the community, these very aspects determining the moral, discipline and human behavior as users of transportation. The purpose of this study is to identify the causes of congestion, knowing the volume of vehicle traffic, knowing the average daily and to find out the capacity at the junction of the black stump road up to the front of the basko grand mall. The highway is a road transport infrastructure play a role very important in the transport sector, especially in the continuity of the distribution of goods and services. To get effective data on traffic volume and road junction up to the front of the black stump basko grand mall to do the survey. Calculation on the road junction of the black stump up front with basko grand mall is done according to the Direktorat Jendral Bina Marga. The peak hours for a motorcycle happened at 17.00-18.00 Gmt bypassed 3795 vehicles. Private car at 17.00-18.00 Gmt with the amount of 1257 vehicles. For Pick up and the Minibus occurred at 07.00-08.00 am passed 380 vehicles. For micro trucks and cars by the groom at 17.00-18.00 Gmt with a population of 75 vehicles. Mini bus or minibus at 17.00-18.00 Gmt with a population of 91 vehicles. For large buses at 17.00-18.00 Gmt with the number of 66 vehicles.